A phenotypic characterization of two isolates of a multidrug - resistant outbreak strain of Mycobacterium tuberculosis with opposite epidemiological fitness - Bei, Jinlong (2020)
Fil: Bei, Jinlong. Guangdong Academy of Agricultural Sciences (GDAAS). AGRO-Biological Gene Research Center, Guangzhou, China.